Sexual dimorphism in anthropometric and fitness measurements of top ju-jitsu contestants - Sterkowicz-Przybycien, K.; Ambrozy, T. (Journal of Combat Sports and Martial Arts, 2013)
The aim of this study was to establish an anthropometric profile and fitness patterns in elite ju-jitsu athletes. Material and methods. The study evaluated 25 elite ju-jitsu athletes (13 males and 12 females). The study participants were divided into the two groups: the heavyweight and lightweight athletes, according to sex. During the tests, 6 anthropometric variables and 12 variables and indices from fitness tests were recorded for each subject. Two-way ANOVA was employed for comparison of the means. The statistical significance level was set at p < 0.05. Effect size and sexual dimorphism index were also calculated. Results. There were significant differences in body height and weight between female and male ju-jitsu athletes, with women typically shorter and lighter than men. Male athletes had higher BMI and FFMI compared to women, who had higher FMI. PF% in female athletes was twice higher than in men. Compared to men, female athletes were characterized by significantly longer times of performing Agility test, Evasion actions and worse on Flexibility tests. Male athletes performed better than female subjects in Handgrip and Push-ups tests. No significant differences were found in other tests between male and female subjects. Conclusions. 1. Despite significant differences in body build and composition, only a locomotor ability, strength endurance and hand grip test differentiated male from female subjects. 2.These findings might be useful for coaches during individual adaptation of training plans, control over the training process and developing new training methods. A knowledge transfer from karate and judo can also be considered.